An Ethnolinguistic Approach for Criticizing Indonesian Interpretations of the Quran - Abdurrahman, Abdurrahman; Rozi, Akh Fahrur (PT. Riset Press International, 2024)
Understanding the holy texts, such as the Quran, requires interpretation. As a means of communication between readers and texts, interpretation is tied to language and culture. To understand the Indonesian interpretation of the Quran, this paper proposes an ethnolinguistic approach. There are two important questions about the position of this approach in research on the interpretation of the Quran in Indonesia and the appropriate research design for this purpose. By using de-contextualization and re-contextualization techniques in library research and meta-analysis techniques, the author succeeded in formulating an ethnolinguistic approach that offers linguistic analysis of interpretation in its cultural context. This allows us to understand the nuances of meaning and the social implications of interpretation. Ethnolinguistic research can help identify cultural and ideological biases in interpretation that open up new interpretive possibilities. This paper discusses appropriate research designs for applying an ethnolinguistic approach to the interpretation of the Quran in Indonesia. Research designs must consider Indonesia’s diverse cultural and linguistic contexts, as well as appropriate data collection and analysis methods. Ethnolinguistic research on the interpretation of the Quran in Indonesia has the potential to make an important contribution to a better understanding of Islam in Indonesia, and its relationship to local culture and language.